To deny or dismantle? Responding to victims of targeted hostility in higher education - Wertans, Emily (International review of victimology, 2024)
With the increasing diversification of higher education, the volume of targeted hostility that students are subjected to on the basis of their identities or perceived ‘differences’ has increased. Typically overlooked within conventional studies of hate crime, incidents of targeted victimisation within higher education are likely to mirror, if not exceed levels exhibited within broader society. Nonetheless, with an absence of robust research evidence exploring this phenomenon, institutions’ responses are often varied, ineffective, or absent. Through a mixed-methods approach involving a survey of 565 student respondents and 39 follow-up interviews undertaken at a UK-based university, this article discusses the nature, impact, and support needs of victims of targeted hostility within higher education. The article unpacks the commonalities and distinctions between victimisation encountered within a campus environment as compared with wider society. Drawing from this study’s research evidence, we argue that while the nature of victimisation within universities holds significant parallels to equivalent encounters within wider society, there are specific challenges within higher education, which can amplify the risk, fear, and impacts of targeted hostility. These challenges require responses within higher education, which acknowledge and prioritise evidence-based, victim-led interventions for prevention, reporting, and support.